More Depression-Related Public Concern After the Suicide of a Pop Star in China: Evidence From the Online Big Data Platform - Yu, Hong-Zhang; Fu, Tian; Zhou, Jia-Nan; Ke, Ping; Wang, Yun-Xia (Frontiers in Psychiatry, 2021)
1) Background: In China, we found a dramatic phenomenon that the depression-related public concern had improved significantly after the suicide of a young pop star. The objective of our study was to examine this phenomenon and explore depression-related search characteristics on the Internet. 2) Methods: According to the time of the suicide of Qiao, the study was divided into two periods. This study collected daily depression, suicide, schizophrenia, obsessive-compulsive disorder, common cold, stomach cancer, and liver cancer-Baidu Index (BDI) and depression-Sina MicroBlog Index (SMI) in two periods. The paired t-test was used to compare the difference between BDI and SMI between two periods. The Pearson correlation coefficient was used to analyze the correlations between the depression-BDI and depression-SMI. 3) Results: The results showed that the average depression-BDI, suicide-BDI and depression-SMI in the second period were significantly higher than the first time period (p <0.05). There was a strong positive correlation between depression-BDI and depression-SMI(r=0.97, p<0.001). The other diseases as comparisons did not show a significant difference between the two periods. 4) Conclusions: This incident involving a celebrity who committed suicide due to depression does significantly improve the public concern about depression in China. On the Internet and social media, we need to provide depression-related professional knowledge and advice to improve public mental health literacy so as to lead the public to cope with their depressive symptoms and its risks appropriately.